PENGARUH SENAM KEGEL TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI TPMB ARISTINA BR MAHA DI LAMPUNG UTARA - Afrina, Dina; Winarni , Winarni (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: A perineal wound is a tear that occurs when a baby is born spontaneously or with an episiotomy. In North Lampung Regency, the incidence of perineal injuries in postpartum mothers is 37%. Kegel exercises are beneficial in helping the healing of the perineal wound in the post partum by alternating contractions and releases in the pelvic floor muscles by making the sutures closer, smoothing blood circulation to the perineum, a clean oxygen-rich blood state is expected to help in the healing of perineal wounds. Objective: To determine the effect of kegel exercises on the healing of perineal wounds in postpartum mothers. Method: This study uses the Quasi Experiment method or pseudo-experiment with a non-equivalent control group research design. The number of samples in this study was 36 respondents using the Mann-Withney statistical test. Results: Based on the results of data analysis using the Mann-Whitney test, the p value was 0.03 < 0.05 which means that there is an effect of kegel exercises on the healing of perineal wounds in postpartum mothers. Conclusion: there is an effect of kegel exercises on the healing of perineal wounds in postpartum mothers